Film Formation of Iodinated Latex Dispersions and Its Role in Their Antimicrobial Activity - Sekar, Hariharan (Langmuir : the ACS journal of surfaces and colloids, 2024)
Waterborne coatings with intrinsic antibacterial attributes have attracted significant attention due to their potential in mitigating microbial contamination while simultaneously addressing the environmental drawbacks of their solvent-based counterparts. Typically, antimicrobial coatings are designed to resist and eliminate microbial threats, encompassing challenges such as biofilm formation, fungal contamination, and proliferation of black mold. Iodine, when solubilized using ethylene glycol and incorporated as a complex into waterborne latex dispersions, has shown remarkable antimicrobial activity. Here, we demonstrate the effect of the film formation process of these iodinated latex dispersions on their antimicrobial properties. The effect of iodine on the surface morphology and mechanical, adhesion, and antimicrobial properties of the generated films was investigated. Complete integration and uniform distribution of iodine in the films were confirmed through UV-vis spectrophotometry and a laser Raman imaging system (LRIS). In terms of properties, iodinated films showed improved mechanical strength and adhesion compared with blank films. Further, the presence of iodine rendered the films rougher, making them susceptible to bacterial adhesion, but interestingly provided enhanced antibiofilm activity. Moreover, thicker films had a lower surface roughness and reduced biofilm growth. These observations are elucidated through the complex interplay among film thickness, surface morphology, and iodine properties. The insights into the interlink between the film formation process and antimicrobial properties of iodinated latex dispersions will facilitate their enhanced application as sustainable alternatives to solvent-based coatings